ACTIVITY OF NITRO-OXIDATIVE PROCESSES IN PREGNANT WOMEN WITH IDIOPATHIC ARTERIAL HYPOTENSION - Leonid Markin; Olena Popovych; Alla Popovych (Acta Medica Leopoliensia)
Primary violation of vascular tone and reactivity is considered the main hemodynamic link in the pathogenesis of idiopathic arterial hypotension (IAH). Two gaseous messengers - nitric oxide (NO) and hydrogen sulfide (H2S) play an important role in the regulation of vascular tone.